Effects of Marijuana Use in Patients with Orthopaedic Trauma. Issue 12 (December 2021) - Sheppard, Sean G.; Wall, Pelle V.; Wheatley, Benjamin; Kent, William
Abstract : The use of cannabis and cannabis-related products has increased dramatically in the last 2 decades. As states continue to legalize cannabis products, it is important for surgeons to understand the effects they may have on patients who have sustained orthopaedic trauma. Cannabinoids have been shown to decrease the severity of certain symptoms related to traumatic brain injury as well as posttraumatic stress disorder. Cannabinoids can modulate the body's endocannabinoid system, which can play an important role in bone homeostasis. Activation of cannabinoid receptors has been shown to be bone-protective in adults. Venous thromboembolism is a major concern for trauma patients. Cannabis use has been linked to overall increased rates of venous thromboembolism events. Literature regarding human-based cannabis studies is sparse; however, the growing field is opening new opportunities for research of this topic.